Kreacja pieniądza kredytowego w warunkach polityki luzowania ilościowegobanków centralnych - Pyka, Irena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The study aims at identification of causes why QE had low impact on the growthof credit money supply in the United States and euro area. The identification ofcauses is supported by analysis of the asset purchase programs implemented byFed and ECB. The differences in the policies are considered the main cause oflower growth of lending in the euro area compared to the US.